SISTEM PEMBAGIAN PUSAKA MENURUT ADAT PERPATIH DALAM PRESPEKTIF MAZHAB SYAFI’I - Jakiran, Jakiran (Fakultas Agama Islam, 2021)
This study uses a bibliographic research approach or research based on literature, the selection of this type is because the data needed are in the form of theories, concepts and ideas about Perpatih customary heritage according to the Syafi'i School. The practice of inheritance distribution to the Perpatih customary community and the implications of this division of perpatih property and the differences that exist between the division of Perpatih property and the Syafi'i school. The inheritance distribution system according to the Perpatih Custom is different from the Islamic inheritance system from the Shafi'i School. According to the Shafi'i school, priority is given to male inheritance for certain reasons, however the female inheritance does not receive from what is owned by male inheritance. The assets belonging to the dead must also be owned as well as goods deposited or credit. After looking at the two inheritance systems and the way of distribution, namely between Perpatih customary law and the Syafi'i school, the author finds that there are differences between the two. Adat Perpatih emphasizes daughters as legal heirs while the Shafi'i School also stipulates sons as legitimate heirs in addition to daughters also having the rights that have been established in Islam. The status of inheritance (customary land) in the Perpatih Adat is as a deposit only. It cannot be sold and pawned, while the heirlooms in the Shafi'i school must be fully owned by someone and if the property is allowed to be sold and pawned.